Análise comparativa do desempenho operacional, econômico e de mercado entre os períodos pré e pós-privatização das companhias brasileiras de distribuição de energia elétrica - Silva, Marcelo Antônio Manget da (2016)
This paper studies the operational, economic and market performance of Brazilian state-owned companies in the electricity distribution sector that were privatized from 1996 to 2000, comparing the results obtained in these three items, for these companies, before and after its privatization. Data analysis period is twenty years, taking as a basis the date of privatization of each company object of the study, backward and forward ten years from that date basis, except in the case of companies whose registration date public company with the CVM, occurred in less than ten years in relation to the dates of their privatization. This paper evaluates these privatized firms are operationally more efficient in relation to its operating performance previous to its privatization; if there was an improvement of the economic indicators of the same making it most profitable companies; and improved market indicators of these companies. Applied hypothesis tests revealed that the operational indicators, and the ratio Sales per Share showed improvement, but there was no evidence to relate these advances to the privatization process. With regard to profit margins, profitability ratios and other market indicators (LPA and VPA), there was no statistical evidence that the privatization impacted positively.